Impaired one-legged landing balance in young female athletes with previous ankle sprain: a cross-sectional study - Petersen, A. K.; Zebis, M. K.; Lauridsen, H. B.; Hölmich, P.; Aagaard, P.; Bencke, J. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Ankle sprain is the most common type of sports injury, especially in team sports. Standing and dynamic landing balance, as an indicator of ankle instability, were investigated using varying experimental approaches. METHODS: In the present cross-sectional study, 81 adolescent female elite handball and football players were divided into two groups based on previous ankle sprain injury (PI) or not (C). At time of test, all players were fully returned to elite-level sport. Subjects were tested during a one-legged landing (OLL) and in a one-legged static standing balance test (OLBT). In the OLL CoP trajectory displacement was calculated in 200 ms time epochs for evaluation of the initial stages of dynamic landing balance. OLBT was evaluated by calculating total displacement of the CoP trajectory. RESULTS: CoP displacement was greater in PI than C during the first 200 milliseconds epoch after landing (P=0.001, 252 mm [44], vs. 223 mm [28]), respectively) and in the subsequent 200 ms epoch (P=0.021, 72 mm [20], vs. 61 mm [16], respectively). No significant differences between PI and C were observed in time epochs from 400 to 1000 milliseconds or in OLBT. CONCLUSIONS: Adolescent elite athletes with a history of previous ankle sprain demonstrate impaired OLL balance in the first 400 milliseconds following jump landing compared to non-injured controls. Consequently, although athletes with previous ankle sprain may return to sport, dynamic postural control may not be fully restored. Future prospective studies are needed to decide, if the OLL test could be considered a relevant criterion tool for safe return-to-sport.